Preparation and Preliminary Evaluation of Neurotensin Radiolabelled with 68Ga and 177Lu as Potential Theranostic Agent for Colon Cancer - Radu Anton Leonte; Livia Elena Chilug; Radu Șerban; Cosmin Mustăciosu; Alina Raicu; Gina Manda; Dana Niculae (MDPI AG, 2021)
The neurotensin is a tridecapeptide involved in the proliferation of colon cancer, the overexpression of neurotensin receptors occurring at an early stage development of many tumours. Targeting neurotensin receptors by using the same biological active molecule is an effective approach for both imaging quantification and treatment. The present work aimed to demonstrate the ability of radiolabelled neurotensin to specifically target colon cancer cells, and substantiate its usefulness in targeted imaging and radiotherapy, depending on the emission of the coupled radioisotope. Syntheses of 68Ga-DOTA-NT and 177Lu-DOTA-NT were developed to obtain a level of quality suitable for preclinical use with consistent high synthesis yields. Radiochemical purity meets the pharmaceutical requirements, and it is maintained 4 h for 68Ga-DOTA-NT and 48 h for 177Lu-DOTA-NT. Extensive in vitro studies were conducted to assess the uptake and retention of 68Ga-DOTA-NT, the amount of non-specific binding of neurotensin and the effect of 177Lu-DOTA-NT on HT-29 cells. In vivo biodistribution of 68Ga-DOTA-NT revealed significant uptake at the tumour site, along with fast clearance evidenced by decreasing activity in kidneys and blood after 60 min p.i. 177Lu-DOTA-NT exhibited similar uptake in the tumour, but also a significant uptake at 14 days p.i. in the bone marrow was reported. These results successfully demonstrated the potential of neurotensin to deliver imaging/therapeutic 68Ga/177Lu radioisotopes pair, but also the need for further evaluation of the possible radiotoxicity effects on the liver, kidneys or bone marrow.